2017
DOI: 10.1128/iai.00087-17
|View full text |Cite
|
Sign up to set email alerts
|

Host Serine/Threonine Kinases mTOR and Protein Kinase C-α Promote InlB-Mediated Entry of Listeria monocytogenes

Abstract: The bacterial pathogen Listeria monocytogenes causes foodborne illnesses resulting in gastroenteritis, meningitis, or abortion. Listeria induces its internalization into some human cells through interaction of the bacterial surface protein InlB with the host receptor tyrosine kinase Met. InlB-dependent entry requires localized polymerization of the host actin cytoskeleton. The signal transduction pathways that act downstream of Met to regulate actin filament assembly or other processes during Listeria uptake r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 44 publications
5
31
0
Order By: Relevance
“…RNA interference was carried out per manufacturer's protocol and as previously described (Bhalla, Law, Dowd, & Ireton, 2017) using cells were seeded in 6-well plates and 24 hr later washed and transfected with siRNA against the above targets at a final concentration of 100 nmol using Lipofectamine2000 (Thermofisher) in FBS-free H292 media. Twelve to 15 hr following transfection, FBS was added to the media at a final concentration of 10%.…”
Section: Knock-down Of A1 Receptor and Pafr By Small Interference Rmentioning
confidence: 99%
“…RNA interference was carried out per manufacturer's protocol and as previously described (Bhalla, Law, Dowd, & Ireton, 2017) using cells were seeded in 6-well plates and 24 hr later washed and transfected with siRNA against the above targets at a final concentration of 100 nmol using Lipofectamine2000 (Thermofisher) in FBS-free H292 media. Twelve to 15 hr following transfection, FBS was added to the media at a final concentration of 10%.…”
Section: Knock-down Of A1 Receptor and Pafr By Small Interference Rmentioning
confidence: 99%
“…Previous results demonstrated that the human serine/threonine kinases mTOR and protein kinase C-␣ (PKC-␣) are activated downstream of Met and play important roles in InlB-mediated entry of Listeria (13). mTOR and PKC-␣ comprise a signaling pathway involved in several biological events, including cell migration and survival (14,15).…”
mentioning
confidence: 99%
“…mTOR forms part of a multicomponent complex called mTORC2 that phosphorylates serine 657 in a hydrophobic motif in PKC-␣, thereby upregulating PKC kinase activity (16). Importantly, InlB-mediated entry of Listeria is accompanied by mTOR-dependent phosphorylation of serine 657 in PKC-␣, indicating that mTOR functions upstream of PKC-␣ during entry (13). How mTOR and PKC-␣ control internalization of Listeria is not well understood.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…After Gab1-mediated or direct interaction with c-Met, activated PI3K mediates Akt activation through phosphorylation of mTORC (67, 68), which, as described above for PRRSV, regulates cytoskeleton dynamics through activation of LIMK-dependent phosphorylation of cofilin (69). PKC- is also activated by mTORC, which is important for L. monocytogenes entry (68). It has been established that some components of the exocytosis machinery play a role in the uptake of L. monocytogenes.…”
Section: Rtk Regulation Of Actin Cytoskeletal Rearrangement During Pamentioning
confidence: 99%